Tracking cashew economically important diseases in the West African region using metagenomics - Monteiro, Filipa; Romeiras, Maria M.; Figueiredo, Andreia; Sebastiana, Mónica; Baldé, Aladje; Catarino, Luís; Batista, Dora (Frontiers in Plant Science, 2015)
During the last decades, agricultural land-uses in West Africa were marked by dramatic shifts in the coverage of individual crops. Nowadays, cashew (Anacardium occidentale L.) is one of the most export-oriented horticulture crops, notably in Guinea-Bissau. Relying heavily on agriculture to increase their income, developing countries have been following a strong trend of moving on from traditional farming systems towards commercial production. Emerging infectious diseases, driven either by adaptation to local conditions or inadvertent importation of plant pathogens, are able to cause tremendous cashew production losses, with economic and social impact of which, in developing countries is often underestimated. Presently, plant genomics with metagenomics as an emergent tool, presents an enormous potential to better characterize diseases by providing extensive knowledge on plant pathogens at a large scale. In this perspective, we address metagenomics as a promising genomic tool to identify cashew fungal associated diseases as well as to discriminate the causal pathogens, aiming at obtaining tools to help design effective strategies for disease control and thus promote the sustainable production of cashew in West African region.